2019
DOI: 10.1089/ast.2018.1997
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Perchlorate on Flight-like Gas Chromatography–Mass Spectrometry as Performed by MOMA on board the ExoMars 2020 Rover

Abstract: The Mars Organic Molecule Analyzer (MOMA) instrument on board ESA's ExoMars 2020 rover will be essential in the search for organic matter. MOMA applies gas chromatography-mass spectrometry (GC-MS) techniques that rely on thermal volatilization. Problematically, perchlorates and chlorates in martian soils and rocks become highly reactive during heating (>200°C) and can lead to oxidation and chlorination of organic compounds, potentially rendering them unidentifiable. Here, we analyzed a synthetic sample (alkano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…In the presence of perchlorates, pyrolysis forms chlorinated molecules and in situ derivatization with MTBSTFA or DMA/DMF is also adversely affected by perchlorates. It has been shown that fatty acids detected through thermochemolysis with TMAH remain unaffected up to 10 wt% perchlorate (Helge Mißbach et al, 2019;He et al, 2021b). However, TMAH has been found to cause isomerization of unsaturated fatty acids, resulting in additional GC peaks (Challinor, 1991).…”
Section: Derivatization For Gas Chromatographymentioning
confidence: 99%
“…In the presence of perchlorates, pyrolysis forms chlorinated molecules and in situ derivatization with MTBSTFA or DMA/DMF is also adversely affected by perchlorates. It has been shown that fatty acids detected through thermochemolysis with TMAH remain unaffected up to 10 wt% perchlorate (Helge Mißbach et al, 2019;He et al, 2021b). However, TMAH has been found to cause isomerization of unsaturated fatty acids, resulting in additional GC peaks (Challinor, 1991).…”
Section: Derivatization For Gas Chromatographymentioning
confidence: 99%
“…Since then, the more advanced pyrolysis-GC-MS of the SAM instrument suite (Mahaffy et al, 2012) has shown that some chlorinated compounds (Freissinet et al, 2015) and more molecularly diverse organic matter (Eigenbrode et al, 2018) are detectable by this approach even when oxychlorines are present, potentially due to a higher carbon to oxychlorine ratio (Kenig et al, 2016). In addition, the search for organic matter on Mars has evolved to include chemical derivatization and thermochemolysis techniques that can enhance the amenability of non-volatile organic compounds to GC-MS (Mahaffy et al, 2012;Mißbach et al, 2019), and laser desorption ionization (LDI) technique of the Mars Organic Molecular Analyzer (MOMA) instrument on board the 2022 ExoMars' Rosalind Franklin rover that circumvents the problem of oxidation of organic compounds during sampling and ionization (Li et al, 2015;Goesmann et al, 2017). These technologies continue to employ mass spectrometers for their high sensitivity in detecting compounds that establish chemical context and enable the search for potential biosignatures.…”
Section: Historical Overview Of Planetary Mass Spectrometrymentioning
confidence: 99%
“…Reagents such as N-methyl-N-tert-butyldimethylsilyl-trifluoroacetamide (MBSTFA) can react with non-volatile polar molecules (e.g., amino acids) to create volatile derivatives amenable to gas analyses, whereas thermochemolysis with reagents such as tetramethylammonium hydroxide (TMAH) in methanol causes hydrolysis followed by methylation, allowing larger analytes to be broken into components with lower molecular weight, enhancing thermal stability and volatility of the reaction products (He et al, 2020). Both of these approaches are currently being employed by SAM onboard the Curiosity rover as part of the MSL mission (Mahaffy et al, 2012;Williams et al, 2019;Millan et al, 2021, accepted) and by the MOMA instrument (Goesmann et al, 2017;Mißbach et al, 2019;Reinhardt et al, 2020). Some methods (e.g., derivatization approaches) may be sensitive to some salts and water (Freissinet et al, 2015;Mißbach et al, 2019) while others (e.g., TMAH thermochemolysis) are more tolerable of both (Mißbach et al, 2019;He et al, 2021).…”
Section: Ionization Sources and Molecular Separation Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…While oxidizing minerals reduce the response for organic matter during thermal extraction, different minerals degrade them to different extents; the detectability of organic matter in a specific sample would depend on organic matter-mineral ratios (Royle et al, 2018a). The problem of oxidizing minerals has resulted in several studies aimed at mitigating the thermal extraction problem, either in the form of exploring alternative organic matter extraction techniques (Mahaffy et al, 2012;Brinckerhoff et al, 2013;Beegle et al, 2015), in situ derivatization (Mißbach et al, 2019), or in the form of sample handling and processing, such as utilizing stepped heating and recording the temperature of release of oxidized carbon (Sephton et al, 2014), and the aqueous leaching of samples to remove soluble oxidizing salts (e.g., perchlorate) (Montgomery et al, 2019).…”
Section: Introductionmentioning
confidence: 99%